Japon des avant-gardes 1910-1970. - Centre Georges Pompidou (Paris : Centre Pompidou, 1986)
Ai-Mitsu ; Arakawa, Shusaku ; Burljuk, David ; Cho Yan-Gyu ; Domoto, Hisao ; Ei-Kyu ; Fujita, Tsuguharu ; Fukuzawa, Ichiro ; Fumon Gyo ; Genpei, Akasegawa ; Hasegawa, Saburo ; Hirohata, Ken ; Imaï, Toshimitsu ; Indo Hisashi ; Inokuma, Gen'ichiro ; Ishigaki Eitaro ; Kanayama, Akira ; Kanbara, Tai ; Kawaguchi, Kigai ; Kawara, On ; Kido Tetsumi ; Kikuhata, Mokuma ; Kitawaki Noboru ; Koga, Harue ; Komaki Gentaro ; Koshimizu, Susumu ; Kosugi, Takehisa ; Kuniyoshi, Yasuo ; Kusama Yayoi ; Lee U-Fan ; Matsuzawa, Yutaka ; Migishi, Kotaro ; Miki, Tomio ; Miyawaki, Aiko ; Motonaga, Sadamasa ; Murai, Masanari ; Murakami, Saburo ; Murayama Tomoyoshi ; Nakada Sadanosuke ; Nakahara Minoru ; Nakamura, Hiroshi ; Nakanishi, Natsuyuki ; Noguchi, Isamu ; Okamoto, Taro ; Okamoto, Toki ; Onchi, Koshiro ; Ono, Yoko ; Onosato, Toshinobu ; Saito, Yoshishige ; Sakata Kazuo ; Sekine, Nobuo ; Shimamoto, Shozo ; Shinohara, Ushio ; Shiraga, Fujiko ; Shiraga, Kazuo ; Suga, Kishio ; Sugai, Kumi ; Tabuchi, Yasukazu ; Takamatsu, Jiro ; Takiguchi Shuzo ; Tanaka, Atsuko ; Terada Masaaki ; Teshigahara, Sofu ; Togo, Seiji ; Tsuruoka, Masao ; Yamaguchi, Takeo ; Yamamoto Keisuke ; Yanase, Masamu ; Yorozu, Tetsugoro ; Yoshida, Yoshio ; Yoshihara, Jiro ; Yoshihara, Michio
boek